2005
DOI: 10.1002/mame.200400287
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gas and Liquid Propylene Polymerization Technique – Hydrogen Effect on Thermal, Rheological, and Morphological Properties of PP

Abstract: Summary: A comparison of PP qualities, which are produced with two different polymerization techniques–gas phase(GP) and liquid pool (LP)–under precise control of the polymerization temperature (70 °C) and pressure (GP = 25 bar, LP < 60 bar) using identical Ziegler‐Natta catalyst (TiCl4/phthalate/MgCl2 + TEA/silane), is presented. A series of homopolymer PP in a wide MW range from 100 000 to 1 600 000 g · mol−1 was polymerized. During polymerization all samples were characterized exactly by their Rp‐profil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…13 The higher melt strength of these copolymers is required for industrial processes such as foaming, thermoforming, or blowmoulding. 49 Poon et al 50 have analyzed the microstructure, morphology, and mechanical properties of propene/hexene copolymers. Furthermore, Arnold et al 51 reported the copolymerization of propene with higher a-olefins up to hexadecene in the presence of the Et(Ind) 2 HfCl 2 /MAO catalyst, and detected the effect of the side chain length on melting points and isotacticities.…”
Section: Branched Polyolefinsmentioning
confidence: 99%
“…13 The higher melt strength of these copolymers is required for industrial processes such as foaming, thermoforming, or blowmoulding. 49 Poon et al 50 have analyzed the microstructure, morphology, and mechanical properties of propene/hexene copolymers. Furthermore, Arnold et al 51 reported the copolymerization of propene with higher a-olefins up to hexadecene in the presence of the Et(Ind) 2 HfCl 2 /MAO catalyst, and detected the effect of the side chain length on melting points and isotacticities.…”
Section: Branched Polyolefinsmentioning
confidence: 99%
“…[39] Before the system was adjusted to the appropriate polymerisation temperature of 70 8C and pressure of about 60 bar, hydrogen was added as a chain transfer agent for controlling the molecular weight. The hydrogen concentration was varied from 0 to 1 500 mg of H 2 to achieve a wide variation of average molecular weight in a range from 101 000 to 1 600 000 g Á mol À1 .…”
Section: Experimental Partmentioning
confidence: 99%
“…Therefore, thermal and rheological data of the LP-PP samples (reported in a previous paper [39] ) were imported into the database. A Cross-WLF viscosity model (Equation (1) and (2)) was used to characterise the temperature and shear rate dependence of viscosity.…”
Section: Simulation Of the Filling Processmentioning
confidence: 99%
“…Besides the variation of the stereoregularity to change the macromolecular profile of poly(propylene), it is interesting to focus on branched poly(propylene)s. Low melt strength is required for industrial processes, such as foaming, thermoforming, or blowmelting. [10] However, Poon et al have analyzed the microstructure, morphology, and mechanical properties of propylene/hexene copolymers. [11] Furthermore, Henschke et al…”
Section: Introductionmentioning
confidence: 99%